The Influence of Gadgets on EFL Student’s Desire to Learn: Transcending the Digital Realm - PUTRI, Auliya Andira; ARHAM, Muhammad (Politeknik Negeri Ujung Pandang, 2024)
The widespread availability of mobile devices and the increasing integration of technology into language education have led to significant changes in the learning landscape. This study examines the impact of gadgets on students' desire to learn and identifies both positive and negative influences, thus providing access to a vast amount of information, facilitating interactive learning experiences, and enhancing motivation through gamification and personalization. Excessive gadget use can lead to distraction, hinder focus, and foster dependence on technology, potentially undermining students' intrinsic motivation and engagement. This systematic literature review aimed to explore the students’ use of gadgets in language education, including their benefits, drawbacks, and effective implementation strategies. As a result, the findings showed that gadgets had a positive influence on students' desire to learn by increasing their engagement and fostering a positive attitude towards their learning. Therefore, educators should adopt a balanced approach that incorporates technology thoughtfully into the learning process. This includes establishing clear guidelines for gadget usage, promoting mindful technology engagement, and fostering a culture of critical thinking and digital literacy.